2020
DOI: 10.1111/wej.12549
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the biochemical effects of an acetamiprid‐based insecticide on a non‐target species, Gambusia holbrooki

Abstract: The toxic effects of an acetamiprid-based insecticide (ABI) on Gambusia holbrooki were evaluated after 24 and 96-h exposure periods. The 24 and 96-h median lethal concentration (LC 50) values of ABI were determined as 75.9 and 42.2 mg/L active ingredient (AI)/L, respectively. In addition, the activity of five biochemical marker enzymes, including glutathione S-transferase (GST), glutathione reductase (GR), carboxylesterase (CaE), lactate dehydrogenase (LDH) and aspartate aminotransferase (AST) was measured aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Supporting these results, imidacloprid exposure reduced GST activity in the gill and kidney of P. lineatus . 18 Demirci and Güngördü 79 reported that acetamiprid caused an increase in GST enzyme activity in Gambusia holbrooki. Thiometoxam significantly increased GST activity in the liver of zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting these results, imidacloprid exposure reduced GST activity in the gill and kidney of P. lineatus . 18 Demirci and Güngördü 79 reported that acetamiprid caused an increase in GST enzyme activity in Gambusia holbrooki. Thiometoxam significantly increased GST activity in the liver of zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…Two references reporting experiments on aquatic organisms were submitted. One acute study (Demirci and Güngördü, 2020 ; RefID 28) consisted of three experiments and evaluated lethal (experiment 1) and biochemical effects of a SP formulation (20% ai) on the non‐target eastern mosquitofish Gambusia holbrooki after 24‐ (experiment 2) and 96‐h (experiment 3) exposure with a renewal of the solution every 24 h. Changes in biomarkers response could only be measured after 24‐ and not 96‐h exposure. The other chronic study (Cossi et al, 2020 ; RefID 16) evaluated the lethal and sublethal toxicity of the technical active substance (experiment 1) and a WP formulation (75% ai, experiment 3) after 14 days of exposure on the non‐target freshwater gastropod Biomphalaria straminea as an indicator species.…”
Section: Environmentmentioning
confidence: 99%
“…In an acute semi‐static study with the eastern mosquitofish (Demirci and Güngördü, 2020 ; RefID 28) over 96 h the LC 50 was calculated as 42.2 mg a.i./L. The external and internal validity for the survival endpoints were considered to have a low risk of bias (class 1, see Figure 7 ).…”
Section: Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, acetamiprid (Aceta) is extensively used in agriculture world-wide, mainly, to control lepidopteran and hemipteran pests in a variety of crops (Guedegba et al 2019 ; Cossi et al 2020 ). The second is imidacloprid pesticide (Imid) which is the most effective, widely and currently the best-selling neonicotinoid insecticide on rice paddies and other crops to control plant and leaf-hoppers, aphids, thrips, and insects (Demirci and Güngördü 2020 ; Naiel et al 2020 ; El-Garawani et al 2021a , b ). Long-term exposure to water contaminants, even at low concentrations, can cause morphological, histological, and biochemical alterations in fish tissues, lowering the quality and marketability of the fish (Haredi et al 2020 ).…”
mentioning
confidence: 99%